Edukasi Pengenalan Apoteker Cilik dan DAGUSIBU Pada Siswa SDN 4 di Desa Bahomoleo Kecamatan Bungku Tengah Kabupaten Morowali - Ismail, Ihwan; Khaerati, Khildah; Yuliet, Yuliet; Yuyun, Yonelian (Jurusan Farmasi FMIPA Universitas Tadulako, 2024)
Pharmacists are pharmaceutical graduates who have completed pharmacy education and have taken the pharmacist oath, carrying out pharmaceutical work including the manufacturing, quality control of pharmaceutical preparations, security, procurement, storage, distribution, or dispensing of drugs, drug management, prescription drug services, drug information services, as well as drug development, drug substances, and traditional medicines. Currently, the empowerment of health education programs and health services at an early age, especially at the elementary school level, has begun to develop. Children need to receive a lot of information about various professions to increase their insights and stimulate their learning spirit. Based on this, education activities of Junior Pharmacists (Apoteker Cilik) and DAGUSIBU (acronym for Obtaining, Using, Storing, and Disposing of drugs properly) were conducted for elementary school students to introduce the pharmacist profession and educate them on obtaining, using, storing, and disposing of drugs properly. The education was conducted for 5th and 6th-grade students at SDN 4 Bungku Tengah, Morowali, Central Sulawesi, involving 60 students. The method of this activity was through PowerPoint presentations, selection of speakers and materials for Junior Pharmacists and DAGUSIBU, and evaluation of education through question and answer sessions on the material. The evaluation results showed a positive outcome, namely an increase in knowledge about the pharmacist profession and proper drug DAGUSIBU.